Pengaruh Penerapan PSAK No. 46 Terhadap Laporan Laba Rugi Pada Tiga Perusahaan Yang Terdaftar di BEI - Kusmala, Abdilla Rahmania; ., Hastoni (Institut Bisnis dan Informatika Kesatuan, 2014)
The company follows a accounting standards generally accepted in drawing up the financial statements, namely Financial accounting standards (SAK). For various reasons, that standard is different from the taxation provisions also utilize accounting information. Due to the difference of a few things in Financial accounting standards (SAK) with the provisions of the Regulation militate in% u2013 Invitation taxation. Bond Accountant Indonesia (IAI) has confirmed the Statements of financial accounting standards (PSAK) No. 46 concerning accounting for income taxes, is a new thing in the accounting standards for enterprises in Indonesia. PSAK No. 46.The purpose of this research is to know concerning PSAK NO. 46 and see if PSAK NO. 46 already applied on the PT Astra International Tbk, PT Mustika Ratu Tbk, PT Mayora Indah Tbk. And how its influence from the application of PSAK NO.46 of the income statement of the company. The study was conducted at the corner of Indonesia stock exchange at STIE Kesatuan Bogor. The results showed that in the application of PSAK NO. 46 will develop assets and deferred tax liabilities interest arising due to temporary differences. The influence of the application of PSAK NO. 46 on the income statements give rise to a difference between the burden of income tax with income tax debt resulting from the existence of differences in recognition of tax-deferred interest assets, which is set to PSAK NO. 46.